Characterization of Metabolic Illnesses and Metabolic Syndrome in an Underserved, Predominantly Hispanic/Latino Population at a Local Student Run Free Clinic - Luke Chi; Anmol Gill; Kashish Chawla; Christine Vu; Roseanne De Guzman; Tanvi Sondhi; Ketaki Lole; Anny Do; Hera Kim; Aarti Dachepalli; Karina Melgar; Andrea Nicholas (Journal of Student-Run Clinics, 2025)
Background: Lestonnac Clinics address a disparity in access to United States healthcare, providing free primary care to underserved populations. Student-run free clinics (SRFCs) consistently report high rates of metabolic illnesses, particularly within Latinx communities. However, research is limited on how these conditions co-occur within SRFC settings, leaving a gap in understanding their interplay and priority areas of care. This study aims to assess metabolic illness prevalence and comorbidity patterns in a SRFC with primarily Latinx patients.Methods: This retrospective study analyzed data from uninsured patients (n=564) seen at a Lestonnac free clinic in Orange County, California, between 2019 and 2021. De-identified electronic health records were collected and included demographics, vitals, body mass index, and diagnoses of diabetes, fatty liver, hyperlipidemia, and hypertension. Statistical analysis using JMP were run including descriptive statistics, prevalence of metabolic illnesses and comorbidities, and Chi-square tests comparing condition proportions between two age groups, <50 years and ≥50 years (p<0.050).Results: Findings revealed differences in diagnosis prevalence between age groups of 564 total patients, with those ages ≥50 showing the higher rates of hyperlipidemia, hypertension, and their co-occurrence, compared to those ages <50. Patients exhibited elevated rates of diabetes (28.7%), and hyperlipidemia (33.2%), surpassing national averages for Hispanic/Latino populations, 11.1% and 10.9%, respectively. However, our clinic demonstrated lower prevalence of fatty liver (15.3%), and hypertension (34.0%) compared to national data, 22.9% and 38.6%, respectively.Conclusion: Our patients aged ≥50 had significantly higher rates of hyperlipidemia, hypertension, and their co-occurrence, while younger cohorts exhibited a high rate of hyperlipidemia. Diabetes and hyperlipidemia rates at our clinic exceeded national averages, underscoring the need for interventions targeting hyperlipidemia prevention in younger cohorts and hypertension, hyperlipidemia, and diabetes management in the aging population. Future research should aim to identify social determinants of health experienced by these patients to enhance prevention effectiveness.